PRIMARY HYPERPARATHYROIDISM IN A PREGNANT PATIENT WITH EPILEPSY: A CASE REPORT - Veerasamy, Hema Lata; Keong, See Chee; Meng, Lim Xue (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Severe hypercalcemia in pregnancy increases the risk of maternal complications and second-trimester fetal loss. Diagnosis of primary hyperparathyroidism during pregnancy is difficult and management of severe hypercalcemia can be challenging. We present a case of primary hyperparathyroidism in a primigravid patient presenting with severe hypercalcemia complicated by recurrent seizure episodes. CASE A 22-year-old primigravida, with a prior history of idiopathic generalized epilepsy, presented at a district hospital with severe hypercalcemia at 26 weeks period of gestation (POG). She had initially presented with multiple episodes of seizures and was incidentally found to have severe hypercalcemia (corrected calcium range: 3.0-3.8 mmol/L). Laboratory investigations revealed elevated serum parathyroid hormone [8.76 pmol/L (1.59-7.24)] and vitamin D insufficiency (25-hydroxy Vitamin D: 63.75 nmol/L). Her calculated calcium-to-creatinine-clearance ratio was 0.02 affirming the diagnosis of primary hyperparathyroidism. Her neck ultrasound revealed no sonographic evidence of parathyroid adenoma. She had repeated admissions during her pregnancy due to severe hypercalcemia coupled with recurrent seizure episodes. She required admission for fluid hydration and loop diuretics to reduce her serum calcium levels. She also required optimization of anti-epilepsy treatment. She was closely monitored by the Endocrine and Obstetric team throughout the pregnancy with a planned delivery by 38 weeks POG. However, she presented one week early in hypertensive crisis, and the breech position of the fetus while in labor, necessitated emergency Caesarean section. She delivered a healthy 2.55 kg baby girl without complications. After delivery, she was treated with intravenous bisphosphonate with her calcium levels improving to 2.4-2.6 mmol/L upon discharge. Functional imaging for localization of possible parathyroid adenoma was planned postpartum. CONCLUSION This case report highlights the challenges in managing severe hypercalcemia during pregnancy in a patient with concomitant recurrent seizures. Close monitoring and multi-disciplinary team communication are important in the management.